Hubungan Literasi Digital Siswa terhadap Implementasi Strategi Diferensiasi dalam Pembelajaran Matematika di Provinsi NTB - Hidayati, Lilik; Sanapiah, Sanapiah (Media Pendidikan Matematika, 2026)
This study aims to analyze the level of students’ digital literacy and its relationship with the implementation of differentiated instruction strategies in mathematics learning in West Nusa Tenggara (NTB) Province. This research uses a quantitative approach with a correlational design. The research sample consisted of 399 junior and senior high school students in NTB Province selected through purposive sampling. The research instrument was a questionnaire covering 8 dimensions of digital literacy and 3 dimensions of differentiated strategies. The results showed that: (1) the level of students’ digital literacy in NTB Province was in the high category with a percentage of 66.9%; and (2) there was a significant relationship between students’ digital literacy and the implementation of differentiated strategies in mathematics learning (r = 0.883, p < 0.05). Digital literacy contributed 88.3% to the implementation of differentiated strategies. These findings indicate that the higher the students’ digital literacy level, the higher their perception of the implementation of differentiated strategies by mathematics teachers. This research recommends the integration of digital literacy strengthening in the planning and implementation of differentiated mathematics learning strategies.